Land Use-Land Cover Changed Analysis in Ogan Watershed, South Sumatra During 2014-2019 Period - Hikmah Utari; Eddy Ibrahim; Edward Saleh; Ngudiantoro (Research Centre of Inorganic Materials and Complexs, 2021)
Land use-land cover (LULC) is one of the indicators commonly used in monitoring the quality of natural resources. Most of the Ogan watershed is a peat ecosystem that plays an important role in maintaining the balance of the ecosystem and water supply. During the 2014-2019 period the Ogan watershed experienced several wildfires and infrastructure development, particularly freeways. This study aims to analyze changes in the LULC in the Ogan watershed during the 2014-2019 period. LULC analysis uses remote sensing technology by utilizing Sentinel and Landsat satellite imagery data. LULC identification used the visual image interpretation method, while LULC changes were analyzed using the GIS technique with the spatial overlay method. The results showed that changes in LULC led to the LULC managed class, where the increase in area occurred in the rubber and oil palm plantation classes. Meanwhile, the highest reduction in area occurred in the dry land forest class. Changes in LULC that occurred during the observation period had a negative impact on the watershed in the form of land degradation, decreased levels of biodiversity and increased fire vulnerability. Based on these results, land use in the Ogan watershed needs to be controlled and land management practices must pay attention to environmental sustainability aspects.